Durability of Fresh Skipjack Fish (Katsuwonus pelamis) by Soaking in Chitosan Solution during Storage at Room Temperature based on Total Volatile Base (TVB) Value - Akerina, Febrina Olivia; Kour, Femsy (Jurnal Ilmiah Platax, 2024)
Fish is a food that easily deteriorates in quality. After the fish is caught or dies, the decomposition process begins to occur, this process lasts 12-20 hours at tropical temperature conditions, depending on the species, fishing method, and fishing equipment. The cause of the decline in fish quality is the activity of bacteria and enzymes by breaking down the components of the fish's body tissue, resulting in physical changes, namely softening of the meat and chemical changes that produce a foul smell due to volatile compounds. This research aims to determine the effect of chitosan solution on the durability of fresh skipjack tuna during storage based on the Total Volatile Base (TVB) value. The results of the research showed that the average TVB content of fresh skipjack tuna from treatment (AB) ranged from 8.48 - 16.78 mg N/100 g, still in the fresh category. BNT follow-up tests showed that the treatment of chitosan concentration and storage time significantly affected the skipjack tuna’s TVB value. Keywords: Demersal fish, organoleptic, pH, Tobelo Abstrak Ikan merupakan bahan pangan yang mudah mengalami kemunduran mutu. setelah ikan ditangkap atau mati, proses pembusukan mulai terjadi, proses ini berlangsung 12-20 jam pada kondisi suhu tropic, tergantung spesies, cara tangkap dan alat penangkapan. penyebab kemunduran mutu ikan adalah aktivitas bakteri dan enzim dengan cara mengurai komponen jaringan tubuh ikan sehingga terjadi perubahan pada fisik  yakni melunaknya daging san perubahan kimia yang menghasilkan bau busuk akibat senyawa-senyawa yang mudah menguap. Penelitian ini bertujuan untuk mengetahui pengaruh larutan kitosan terhadap daya awet ikan cakalang segar selama penyimpanan berdasarkan nilai Total Volatile Base (TVB). Hasil penelitian menunjukkan bahwa rata – rata kandungan TVB ikan cakalang segar dari perlakuan (AB) berkisar antara 8,48 – 16,78 mg N/100 g masih dalam kategori segar Uji lanjut BNT menunjukkan perlakukan konsentrasi kitosan dan lama penyimpanan berpengaruh nyata pada nilai TVB ikan cakalang segar. Kata kunci : Ikan cakalang, nilai TVB, Tobelo.